Scientific and methodological foundations of open educational platform employment in language teaching - Abnassyrova, Raikhan; Mubarak, Nazerke; Ordabekova, Khafiza; Turumbetova, Zhanagul; Mukhamadi, Kuralay (International Journal of Evaluation and Research in Education (IJERE), 2025)
The objective of the research is to investigate the efficacy of these platforms in facilitating language acquisition, fostering student engagement, and personalizing learning experiences. A survey was conducted among 100 language teachers from higher educational institutions in Astana, Kazakhstan. The teachers were requested to evaluate the efficacy of open platforms in language instruction, taking into account factors such as student motivation, the individualization of learning, and the availability of resources. The research employed a descriptive design, utilizing a three-level response scale to collect data on the integration of the aforementioned platforms and the preparedness of educators to utilize them. The findings suggest that open platforms facilitate access to resources and enhance student motivation when integrated with interactive tools, such as GraphoLearn and Kahoot!. However, the study emphasizes the necessity for structured training to address the challenges encountered by educators in implementing these platforms effectively.